2006
DOI: 10.1007/s10620-006-3096-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Pentagastrin-Stimulated Gastric Acid Secretion by Pantoprazole and Omeprazole in Healthy Adults

Abstract: Our objective was to compare the onset and duration of a single dose of pantoprazole or omeprazole on maximally stimulated gastric acid secretion. This double-blind, randomized, placebo-controlled study involved 36 healthy adults and utilized continuous pentagastrin infusion to stimulate acid secretion after administration of pantoprazole, 40 mg, omeprazole, 20 mg, or placebo. Gastric aspirates were collected over 24 hr and analyzed for volume, pH, and hydrogen ion concentration, and gastric acid outputs (GAO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…49 A recent study by Pratha et al, showed that when gastric pH is >2.5, gastric acid secretion is always <2 mmol ⁄ h. Thus, 'fasting' weakly acidic reflux in patients 'on' PPI may have a similar volume to that of acid reflux but might be composed by duodenal secretion and ⁄ or saliva (gastric bicarbonate secretion is very low). 50 In contrast, the volume of 'postprandial' weakly acidic reflux seems to be more related to postprandial gastric contents (meal, duodenal material and saliva).…”
Section: Volume Of Reflux and Gerd Symptoms: Direct Measurementsmentioning
confidence: 97%
“…49 A recent study by Pratha et al, showed that when gastric pH is >2.5, gastric acid secretion is always <2 mmol ⁄ h. Thus, 'fasting' weakly acidic reflux in patients 'on' PPI may have a similar volume to that of acid reflux but might be composed by duodenal secretion and ⁄ or saliva (gastric bicarbonate secretion is very low). 50 In contrast, the volume of 'postprandial' weakly acidic reflux seems to be more related to postprandial gastric contents (meal, duodenal material and saliva).…”
Section: Volume Of Reflux and Gerd Symptoms: Direct Measurementsmentioning
confidence: 97%
“…The supernatant was then analysed for determination of pH according to the method of Hara et al (16), free and total acid concentrations were estimated by using the method of Pratha et al (17) and pepsin concentrations were determined by a modifi ed spectrophotometric method (18).…”
Section: Analysis Of the Gastric Juicementioning
confidence: 99%
“…MAO is the maximum gastric acid (mmol/h) that is secreted after a potent stimulus for the secretion of gastric acid. In a previous study, pantoprazole patients reached and maintained GAO levels below the 10.0 mmol/h threshold at 5.7 h after a single oral dose 9 …”
Section: Introductionmentioning
confidence: 79%